UK dietary exposure to PCDD/Fs, PCBs, PBDD/Fs, PBBs and PBDEs: comparison of results from 24-h duplicate diets and total diet studies. Issue 1 (2nd January 2017) - Bramwell, Lindsay; Mortimer, David; Rose, Martin; Fernandes, Alwyn; Harrad, Stuart; Pless-Mulloli, Tanja
ABSTRACT: Chemicals in food are monitored to check for compliance with regulatory limits and to evaluate trends in dietary exposures, among other reasons. This study compared two different methods for estimating human dietary exposure to lipophilic persistent organic pollutants (POPs) during 2011/12: (1) the 2012 Total Diet Study (TDS) conducted by the UK Food Standards Agency (FSA) and (2) a 24-h duplicate diet (DD) study of 20 adults from the North East of England. The equivalence of the two approaches was assessed; anything less than an order of magnitude could be considered reasonable and within three-fold (equivalent to 0.5 log) as good. Adult dietary exposure estimates derived from the DD study for both average and high-level (97.5th percentile) consumers compared well with those from the TDS. Estimates from the DD study when compared with those from the TDS were within 10% for P97.5 for total PCDD/F/PCB with divergence increasing to a factor of 3.4 for average BDE-209. Most estimates derived from the TDS were slightly higher than those derived from the DD. Comparison with earlier UK TDS data over the last 30 years or so confirmed a gradual decline in levels of PCDD/F/PCBs in food. Such comparisons also indicated peaks in dietary exposure to ∑PBDE (excluding BDE-209) between 2000 and 2005. Exposure estimates for all measured compounds using both TDS and DD data were found to be within recommended tolerable daily intakes where available or within acceptable margins of exposure.